Projeto Sensível ao Valor centrado no Afeto (PSV_A): base teórico-metodológica para a projetação afe(c)tiva de ambientes hospitalares - Duarte, Imara Angélica Macêdo (2024)
Planned as spaces for health recovery, hospitals are sources of traumatic, stressful and perceived as threatening experiences, which involve pain, loss of control, disorientation, lack of physical comfort and deprivation of family surroundings. In this context, the environmental response is part of the first level of the affective dimension with direct impacts on the physiological process and the modulation of environmental cognition, a central situation in the person-environment relationship. In this sense, the objective of the thesis is to present a contribution to the formation of a theoretical-methodological model, denominated 'Value-Sensitive Project centered on Affect' (PSV_A, in portuguese), based on Spinoza's philosophy of affect, the theory of Restorative Environments and Value Sensitive Design, which works as an aid to designers when planning hospital environments, in a way that considers the user's affective dimension. The proposed framework was administered through thematic workshops, with young professionals in an academic environment, and in a collaborative manner. The results suggest that the approach and its administration are promising, and that there is an opportunity for its inclusion in the Architecture and Urban Planning course curriculum. It is also understood that the improvement of the PSV_A in a real, progressive and iterative situation, will possibly smooth conceptual and pragmatic edges so that the exercise of affective projection can become part of the education of young architects.